An analysis of slang language used in raditya dika’s podcast - Delpia, Fila; Pasaribu, Tiara k.; Sembiring, Rony Arahta (Universitas Pahlawan Tuanku Tambusai, 2024)
Language is the most important means of communication in life, whether in the form of writing, orally, or only in the form of certain signs. Without language, humans cannot socialize with other people and slang is a phenomenon of the use of linguistic variations that are formed as a result of language development and social dynamics in society. Slang is a new vocabulary owned by a certain group of people that is related to informal conversations and used in informal situations. This research aims to find out the types and meanings of slang contained in Raditya Dika's podcast. The data source for this research was taken from Raditya Dika's podcast which was uploaded to his Spotify account with the title